The relationship between political efficacy and online political participation among women: a systematic literature review - Liu, Yu; Ku Samsu, Ku Hasnita; Lee, Yok Fee; Ismail, Mohd Mahadee (Universiti Sains Islam Malaysia, 2024)
Despite persistent challenges in women’s political participation, online political participation (OPP) has created new opportunities, with women’s efficacy in changing political processes. However, the results of the studies on OPP and political efficacy (PE) among women are varied. While existing literature suggests a strong correlation between political efficacy (PE) and OPP behaviours, a systematic analysis of women as a marginalised group is lacking. This study addresses this gap by critically examining the types, theories, variables, and research frameworks related to PE and OPP among women, aiming to construct a comprehensive causal framework. Using the PRISMA, the researchers systematically reviewed ten peer-reviewed articles (2014-2023) from Web of Science (WOS) and Scopus. The analysis revealed diverse dimensions of PE and OPP. PE encompassed internal (IPE), external (EPE), online (OPE), and collective political efficacy (CPE), with IPE most frequently studied. OPP behaviours were categorised into active and passive forms, with online political expression predominating. The theoretical frameworks covered five theories across psychology, political science, and mass media. Results indicated that while OPP did not predict PE, PE significantly predicted OPP. The study identified differences based on democratic contexts, suggesting the need for subtle approaches in future. This review contributes to the field by synthesising current knowledge, elucidating the interplay of relevant variables, and highlighting critical gaps in the literature. By providing a holistic understanding of the PE-OPP relationship among women, this study offers valuable insights for researchers and policymakers.